2019
DOI: 10.1136/archdischild-2018-315644
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of conventional and videolaryngoscopy blades in neonates

Abstract: Neonatal intubation is an essential but difficult skill to learn. Videolaryngoscopy allows the airway view to be shared by the intubator and supervisor and improves intubation success. Ideally, a videolaryngoscope (VL) should be usable as a conventional laryngoscope (CL). The aims of this report were to describe differences in the shape of currently available CL and VL blades and to compare the direct airway view obtainable on a neonatal manikin with different laryngoscope blades.Three main differences were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Although few studies have reported that chest compressions may not interrupt the intubation process (30,31), which is similar to the results of our study, it is important to reduce the risk of injury and relieve the stress of the intubator when continuous chest compressions are necessary. VL may improve the intubation time by providing a good view of the glottis compared with DL under the circumstances of uninterrupted chest compressions (32). These studies, including ours, reflect the performance of resuscitators or trainees in intubating manikins.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Although few studies have reported that chest compressions may not interrupt the intubation process (30,31), which is similar to the results of our study, it is important to reduce the risk of injury and relieve the stress of the intubator when continuous chest compressions are necessary. VL may improve the intubation time by providing a good view of the glottis compared with DL under the circumstances of uninterrupted chest compressions (32). These studies, including ours, reflect the performance of resuscitators or trainees in intubating manikins.…”
Section: Discussionmentioning
confidence: 66%
“…One-third of the trainees with intubation experience favored its use as a result of the minor adaptation of visualization for intubation. The blade of the video laryngoscope may be designed to minimize the possibility of intubation-associated injury since the vocal cord do not have to be visualized for intubation ( 33 ). This method may help operators predict the difficulty of intubation ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of difficult airway, when it is impossible to optimally visualize the entrance to the glottis, difficult intubation stylets can be helpful, allowing the intubation tube to be inserted into the trachea without the need to visualize it. Intubation with a Miller or Macintosh blade laryngoscope was insufficiently effective under difficult airway conditions and the duration of the procedure was prolonged as compared with intubation with the use of a stylet or videolaryngoscope [3941].…”
Section: Discussionmentioning
confidence: 99%
“…Videolaryngoscope (VL) (35) and supraglottic airway devices (SAD) such as LMA (36) are increasingly used in neonates (37, 38) as companies develop equipment for use at lower gestations (39,40). LMA is recommended in the 2020 European Resuscitation Council (ERC) guidelines as an adjunct in infants of 34 weeks gestation or more (17).…”
Section: Other Airway Adjunctsmentioning
confidence: 99%